Effectiveness and cost-effectiveness of a self-management training for patients with chronic and treatment resistant anxiety or depressive disorders: design of a multicenter randomized controlled trial. Issue 1 (December 2016) - Zoun, Maringa; Koekkoek, Bauke; Sinnema, Henny; Muntingh, Anna; van Balkom, Anton; Schene, Aart; Smit, Filip; Spijker, Jan
Abstract Background Many patients with anxiety or depressive disorders achieve no remission of their symptoms after evidence-based treatment algorithms. They develop a chronic course of the disorder. Current care for these patients usually consists of long-term supportive contacts with a community psychiatric nurse and pharmacological management by a psychiatrist. Data on the effectiveness of these treatments is lacking. A psychosocial rehabilitation approach, where self-management is an increasingly important part, could be more suitable. It focuses on the restoration of functioning and enhancement of patients' autonomy and responsibility. Treatment with this focus, followed by referral to primary care, may be more (cost-)effective. Methods A multicenter randomized controlled trial is designed for twelve participating specialized outpatient mental health services in the Netherlands. Patients with chronic and treatment resistant anxiety or depressive disorders, currently receiving supportive care in specialized outpatient mental health care, are asked to participate. After inclusion, patients receive the baseline questionnaire and are randomized to the intervention group or the usual care control group. The intervention focuses on rehabilitation and self-management and is provided by a trained community psychiatric nurse, followed by referral to primary care. Measurements take place at 6, 12, and 18 months after baseline. This study evaluates both the effectiveness (on quality of life, symptom severity, and empowerment), and cost-effectiveness of the intervention compared to usual care. In addition, a questionnaire is designed to get insight in which self-management strategies patients use to manage their disorder, and in the experiences of patients with the change of care setting. Discussion In this study we evaluate the effectiveness and cost-effectiveness of a self-management intervention for patients with chronic and treatment resistant anxiety or depressive disorders in specialized outpatient mental health care. The results of this study may provide a first 'proof-of-concept' in this under-researched but important field, and might be relevant for a large group of patients in the context of a transition of the Dutch health care system. Trial registration Netherlands Trial Register:NTR3335, registered 7 March 2012.